Pemanfaatan Media Youtube dalam Pembelajaran Bahasa Indonesia bagi Guru-Guru Sekolah Menengah Pertama - Baadilla, Irwan; Sulistyawati, Rr.; Amalia, Nur; Ibrahim, Nini; Hidayatullah, Ahmad (Empowerment, 2023)
YouTube is important as a learning media for the Indonesian language. Training on YouTube utilization is crucial for junior high school teachers to enhance their teaching abilities. Mastering YouTube as an innovative learning platform is essential for teachers, although there are still challenges in its implementation. This activity aims to improve teachers' knowledge and skills in utilizing YouTube as a medium for teaching Indonesian language. The training combines seminar methods with direct mentoring. Evaluation through a final test indicates that teachers who participated in the training successfully enhanced their understanding and abilities in utilizing YouTube for Indonesian language instruction. In conclusion, this community service activity was carried out successfully and effectively in enhancing teachers' skills, influenced by the commitment of the FKIP UHAMKA Community Service Team and the collaboration with SMP Muhammadiyah Cisalak.YouTube penting sebagai media pembelajaran bahasa Indonesia. Pelatihan pemanfaatan YouTube penting bagi guru-guru SMP untuk meningkatkan kemampuan mengajar. Penguasaan YouTube sebagai media pembelajaran inovatif merupakan hal penting bagi guru, namun masih terdapat kendala dalam penerapannya. Kegiatan ini bertujuan meningkatkan pengetahuan dan keterampilan guru dalam memanfaatkan YouTube sebagai media pembelajaran bahasa Indonesia. Kegiatan pelatihan ini menggabungkan metode seminar dan pendampingan langsung. Evaluasi melalui tes akhir menunjukkan bahwa para guru yang mengikuti pelatihan berhasil meningkatkan pemahaman dan kemampuannya dalam memanfaatkan YouTube dalam pembelajaran bahasa Indonesia. Simpulannya ialah kegiatan pengmas ini berhasil dan sukses dijalankan untuk meningkatkan kemampuan guru yang dipengaruhi oleh komitmen Tim Pengmas FKIP UHAMKA dan kerjasama dengan SMP Muhammadiyah Cisalak.